Acellular Extracellular Matrix Bioscaffolds for Cardiac Repair and Regeneration - Pattar, Simranjit S.; Fatehi Hassanabad, Ali; Fedak, Paul W. M. (Frontiers in Cell and Developmental Biology, 2019)
Heart failure is a progressive deterioration of cardiac pump function over time and is often a manifestation of ischemic injury caused by myocardial infarction (MI). Post-MI, structural remodeling of the infarcted myocardium ensues. Dysregulation of extracellular matrix (ECM) homeostasis is a hallmark of structural cardiac remodeling and is largely driven by cardiac fibroblast activation. While initially adaptive, structural cardiac remodeling leads to irreversible heart failure due to the progressive loss of cardiac function. Loss of pump function is associated with myocardial fibrosis, wall thinning, and left ventricular (LV) dilatation. Surgical revascularization of the damaged myocardium via coronary artery bypass graft (CABG) surgery and/or percutaneous coronary intervention (PCI) can enhance myocardial perfusion and is beneficial. However, these interventions alone are unable to prevent progressive fibrotic remodeling and loss of heart function that leads to clinical end-stage heart failure. Acellular biologic ECM scaffolds can be surgically implanted onto injured myocardial regions during open-heart surgery as an adjunct therapy to surgical revascularization. This presents a novel therapeutic approach to alter maladaptive remodelling and promote functional recovery. Acellular ECM bioscaffolds have been shown to provide passive structural support to the damaged myocardium and also to act as a dynamic bioactive reservoir capable of promoting endogenous mechanisms of tissue repair, such as vasculogenesis. The composition and structure of xenogenic acellular ECM bioscaffolds are determined by the physiological requirements of the tissue from which they are derived. The capacity of different tissue-derived acellular bioscaffolds to attenuate cardiac remodeling and restore ECM homeostasis after injury may depend on such properties. Accordingly, the search and discovery of an optimal ECM bioscaffold for use in cardiac repair is warranted and may be facilitated by comparing bioscaffolds. This review will provide a summary of the acellular ECM bioscaffolds currently available for use in cardiac surgery with a focus on how they attenuate cardiac remodeling by providing the necessary environmental cues to promote endogenous mechanisms of tissue repair.